Japanese trade &​ industry in the Meiji-Taisho era : - Keishi, Ohara (Ōbunsha, 1957)
PART ONE: GENERAL OUTLINE ; PART TWO: THE OPENING OF THE PORTS AND EARLY TRADE RELATIONS BETWEEN JAPAN AND TH UNITED STATE....